Double solutions and stability analysis of slip flow past a stretching/shrinking sheet in a carbon nanotube - N. H. A, Norzawary; N., Bachok; F. M., Ali; N. A. A., Rahmin (Lviv Polytechnic National University, 2022)
A stagnation point flow past a stretching/shrinking surface in carbon nanotubes (CNTs) with slip effects is investigated in this paper. Applying transformations of similarity, the governing partial differential equations are modified to the nonlinear ordinary differential equations. Afterward, they are numerically solved in Matlab by the bvp4c solver. The single-wall CNTs and multi-wall CNTs are used, including water as a base fluid. The effects of the flow parameters are investigated, shown in the form of graphs, and physically evaluated for the dimensionless velocity, temperature, skin friction, and Nusselt numbers. According to our findings, the unique solution exists for stretching sheets, whereas non-unique solutions are obtainable for shrinking sheets. The stability analysis is utilized to discover which solution is stable.